The Socio-Economic Impact of e-governance: Indian Scenario - V.J. Ravi Kumar, Dr. B.Deevena Margaret, (International Journal of Scientific Research and Management (IJSRM), 2015)
Today Information Communication Technology (ICT) constitutes the fastest growing component of the global economy and the revenue generated by the interactive information industry may have reached $3.5 trillion. Recently, the Indian Government has set the target of delivering at least 25 percent of its dealings and services electronically. In this regard, the Indian Government’s major policy measures have been defined in terms of computer density, connectivity, content, cost and cyber laws. E-Government can advance the agenda on governance and economic reform, transparency, anti-corruption, empowerment and poverty reduction. In conclusion, one needs to understand that after two decades of e-commerce, e-governance and e-citizen, India remains one of the poorest countries in the world with 44.3 percent adult literacy rate, 25 percent people without health services, 71 percent without access to sanitation, 35 percent living below the poverty line, $100 billion external debt and 128th rank in the recent Human Development Index E-governance must show more than this dismal scenario of human conditions in India. But it is yet to be seen whether e-governance can eradicate poverty, reduce inequality and satisfy basic human needs in a poor country like India.